2021
DOI: 10.1016/j.jafr.2021.100102
|View full text |Cite
|
Sign up to set email alerts
|

What is required to scale-up and sustain biofortification? Achievements, challenges and lessons from scaling-up Orange-Fleshed Sweetpotato in Sub-Sahara Africa

Abstract: This review presents results of the ex-post survey on Reaching Agents of Change (RAC) project, highlighting experiences, lessons, challenges and recommendations for scaling up orange-fleshed sweetpotato (OFSP). The RAC project was a three-and halfyear initiative (2011 and 2015), implemented in three primary countries, namely Tanzania, Mozambique, Nigeria, and to a lesser extent Ghana and Burkina Faso. The project advocated for policy change and increased investments to scale-up the orangefleshed sweetpotato (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The RAC project was a 3.5-year initiative (2011–2015) that advocated for policy change and increased investments, including advocacy toolkits to scale up OSP to combat vitamin A deficiency; the design and history of this project are described in a recent review [ 34 ]. In an ex-post survey of the RAC project, it was noted that production of OSP has remained on a largely small scale (land sizes 1 acre to 1.5 acres) and is predominantly used for home consumption [ 34 ]. However, the resulting effects of the study are ongoing and are expected to benefit at least 600,000 households directly, having reached 309,974 direct beneficiaries thus far in 2021.…”
Section: Resultsmentioning
confidence: 99%
“…The RAC project was a 3.5-year initiative (2011–2015) that advocated for policy change and increased investments, including advocacy toolkits to scale up OSP to combat vitamin A deficiency; the design and history of this project are described in a recent review [ 34 ]. In an ex-post survey of the RAC project, it was noted that production of OSP has remained on a largely small scale (land sizes 1 acre to 1.5 acres) and is predominantly used for home consumption [ 34 ]. However, the resulting effects of the study are ongoing and are expected to benefit at least 600,000 households directly, having reached 309,974 direct beneficiaries thus far in 2021.…”
Section: Resultsmentioning
confidence: 99%
“…The NMNAP specifically aims to promote the cultivation and consumption of biofortified high-protein maize and cassava as well as vitamin A-enriched orange-fleshed sweet potato and bananas by focusing on the multiplication and distribution of seeds, seedlings, and cuttings of nutrient-dense crop varieties among farmers. Moreover, under the National Food Fortification Alliance (NFFA), the National Biofortification Task Force was formed to advocate for biofortification projects to alleviate malnutrition in Tanzania, while in Nigeria, projects like Working to Improve Nutrition in Northern Nigeria (WINNN) and the Rainbow Project played a significant role in including biofortified crops in national plans and policies [201].…”
Section: Policy Support To Promote Biofortified Cultivarsmentioning
confidence: 99%
“…However, some orange-fleshed varieties have a high content of dry matter, as well as a content of beta-carotene high enough to meet a person’s required dietary allowance [ 13 , 14 , 21 , 28 ]. The majority of farmers tend to cultivate white-fleshed sweet potatoes, which a have high dry matter content, low water content, and low beta-carotene content compared with orange-fleshed sweet potato genotypes, which have higher water content and beta-carotene content but a lower dry matter content [ 29 ]. Several authors have reported fluctuations in the nutritional quality and content of cereals, such as maize, millet, rice, wheat, and barley, which have been attributed to climate change [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%